Islamic Education Reform In The Middle East: Tradition and Modernization in Education in Saudi Arabia, Egypt, and Turkey - Fadhluzzakiyy, Kemas Ahmad; Munir, Munir; Nurlaila, Nurlaila (STAI Serdang Lubuk Pakam, 2025)
This abstract aims to analyze the process of Islamic education reform in three Middle Eastern countries, namely Saudi Arabia, Egypt, and Turkey, which face challenges in balancing the preservation of traditional Islamic values and the need for modernization based on science and technology. This study uses a qualitative approach with literature review to explore educational policies and socio-political dynamics that influence the transformation of Islamic education in the three countries. The findings reveal that Saudi Arabia, through its Vision 2030, focuses on moderating religious teachings and reforming the curriculum to create a globally competitive generation. Egypt attempts to integrate Al-Azhar education with the secular education system despite facing epistemological dualism. Turkey strengthens Islamic education through Imam Hatip schools under a secular state framework. This study identifies that the success of educational reform is greatly influenced by political and ideological contexts and the readiness of human resources. The implications of this study include the importance of curriculum flexibility and teacher training to respond to the challenges of the 21st century.